Silicon doping of HVPE GaN bulk-crystals avoiding tensile strain generation. (28th January 2016) - Hofmann, Patrick; Röder, Christian; Habel, Frank; Leibiger, Gunnar; Beyer, Franziska C; Gärtner, Günter; Eichler, Stefan; Mikolajick, Thomas
Abstract: Doped GaN:Si crystals were grown in a commercially available vertical HVPE reactor. The templates used for the HVPE heteroepitaxy were so-called FACELO seeds, with a starting GaN layer thickness of 3–4 μ m. The FWHM of the 0002 and the reflection of the HVPE-grown GaN:Si crystals with a thickness of 3 mm are and, respectively, indicating excellent crystal quality. Hall measurements resulted in a charge carrier concentration of cm −3, while exhibiting a mobility of 250 cm −2 V −1 s −1 . These values coincide with the values extracted from FTIR measurements and the lineshape fitting of the A1 (LO)/plasmon coupled phonon mode of the confocal Raman measurements. SIMS investigations yielded a silicon atom concentration of cm −3 . This indicates an activation of the dopant atoms of approximately 90%. The TDD determined by CL dark spot counting was cm −2 . Within the measurement accuracy, the confocal Raman measurements did not show a tensile strain generation due to the silicon doping with resulting charge carrier concentrations of cm −3 .